Characterization of Soil Properties in Relation To Growth Performance of Planted Shorea macrophylla After Enrichment Planting Under Sandy Soil at Sabal Forest Reserve, Sarawak, Malaysia - Izwaida, Che Adanan (Universiti Malaysia Sarawak (UNIMAS), 2020)
Assessment on the soil condition and growth performance of the planted tree on degraded forest, particularly on the sandy soil, is crucial in providing more information on the current status of the reforestation site. Hence, the aims of this study were to characterize the soil properties in term soil morphological properties and soil physicochemical properties at the reforestation site in comparison with high conservation forest as well as to determine growth performance of planted Shorea macrophylla at the reforestation sites under sandy soil. This study were involved two reforestation sites ((Early Estalishment of Reforestation Site (ER) and Late Establishment of Reforestation Site (LR)) and two High Conservation Forests (High Conservation Forest 1 (HCF 1) and High Conservation Forest 2 (HCF 2) as a control. Study plot with the size of 25 m x 25 m were contructed randomly on a reforestation site planted with S. macrophylla and High Conservation Forest at Sabal Forest Reserve. For soil morphological properties assessment, soil profile with the soil depth of approximately 100 cm depth was dug at the center of each study sites. As for soil physicochemical properties, soil composites were randomly collected at the soil depth of 0-10 cm and 30-40 cm by using a soil auger. Standard soil analysis for soil physical and chemical properties was performed. Diameter at Breast Height (DBH), total height and survival percentage of the planted S. macrophylla in the reforestation site were measured. The results from soil morphological properties showed that the soils in ER and HCF-2 plot were resemble Saratok series under Grey-White Podzolic soils (Ultisols) in which, corresponds to Typic Paleaquults of Soil Taxonomy by USDA Classification. Meanwhile, the soils in LR and HCF-1 plot were classified under Buso series of the Podzols which corresponds to Typic Haplothods of Spodosols under the USDA classification system. As for soil physicochemical properties, soils at study sites were strongly acidic in nature with pH (H2O) value less than 5.00 at both surface and subsurface soils. Besides, the sand content in ER and HCF-2 plots were less than 73%, meanwhile the sand content in LR and HCF-1 plots were more than 80% at both surface and subsurface soils. Although the soil in the study sites chacterized as acidic, sandy and low nutrient content, the growth performance of planted S. macrophylla still can survive. Based on the survival percentage of planted S. macrophylla in the ER and LR plot were 65 % and 56%, respectively. This can be concluded that S. macrophylla is suitable indigenous tree species to be planted in reforestation activities in the future especially under sandy soil. Nonetheless, it is recommended that long term monitoring on the soil properties and growth performance of planted S. macrophylla are essential in order to continuously provide information on the status of reforestation activity.